Effect of Paclobutrazol and Gandasil Fertilizers on the Growth and Yield of Cayenne Peppers (Capsicum frutescens L.) in Urban Farming - Aisyah Shinta Nila Sari; Agus Sulistyono; Felicitas Deru Dewanti (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Cayenne pepper cultivation in urban areas faces several obstacles, including infertile soil, irregular watering due to busy daily activities, pests and diseases that spread more easily in urban areas, and high temperature changes. This study aims to obtain the optimal concentration of paclobutrazol and Gandasil fertilizer for the development and production of cayenne pepper. This study used a factorial completely randomized design with two factors, namely paclobutrazol concentration consisting of 4 levels (0 ppm, 75 ppm, 100 ppm, and 125 ppm) and Gandasil B/D fertilizer consisting of 4 levels (1 g/L, 2 g/L, 3 g/L, and 4 g/L). Results showed that treatment combination of paclobutrazol 100 ppm and Gandasil 3 g/L gave the best results on the number of flowers per plant (822.0), number of fruits per plant (144.5), and fruit weight (156.77 g/plant). This combination may, however, result in low fruit yield and inhibit vegetative development, including leaf number and plant height. The fastest flowering age was obtained at combination paclobutrazol 125 ppm and Gandasil concentrations of 4 g/L with a value of 39.33 days.   Keywords: Concentration, Gandasil fertilizer, Growth, Paclobutrazol, Yield.